Constructivism in the pedagogical and epistemological conceptions of teachers (Revista Innova Educación, 2020)
In recent years, pedagogical constructivism has enjoyed great popularity, so that many people recognize themselves as constructivists. In the literature it was found that many teachers reported having conceptions aligned to this paradigm, however, the results are contradictory in this regard. In this sense, the purpose of this work was to deepen the results of such research on teaching conceptions, specifically tracing a constructivist view of their practice, as well as the recommendations that the experts have made with regard to these results. A systematic review of the literature was carried out. Documents were searched in the Dialnet database. After applying different filters and assessing the relevance of the articles, 13 works were admitted for qualitative and quantitative analysis. Among the main results, it is emphasized that teachers maintain epistemological and pedagogical conceptions formed by different paradigms, which are not always coherent with each other, but present diffuse limits. For this reason, interventions are recommended that: 1) review paradigmatic differences at the theoretical level, 2) allow teachers to reflect on their conceptions and help them to externalize them, and 3) implement practical models in accordance with institutionally desirable scientific or pedagogical paradigms. It presents theoretical material organized with respect to constructivism to guide the first two phases.
Keywords: Constructivism; teaching conceptions; systematic review